Global-mindedness Through the Eyes of EFL Learners: Gender and Level of Proficiency in Focus - Fatalaki Javad Ahmadi; Zhang Runhan (East European Journal of Psycholinguistics, 2016)
The major aim of the present study is to find connections between global-mindedness and some important factors such as gender  and level of proficiency. To this end, 182 language learners, 92 females and 90 males, participated in the study. These students were selected and categorized based on one-stage cluster sampling from 16 branches of different language centers, namely Safiran, Shoukoh, and Kish. The main phase of the study was conducted through the use of Google Docs platform that provides the researchers with the well-organized data. Language learners were asked to answer all the demographic information by considering their anonymity during the process of data collection. The result of the study, through t-test, showed that there was a significant difference between male and female language learners regarding their level of global-mindedness. The result also showed that the level of proficiency of the female language learners does not influence their level of global-mindedness.ReferencesByram, M., Zarate, G., & Neuner, G. (1997). Sociocultural competence in languagelearning and teaching: Studies towards a common European framework of reference forlanguage learning and teaching. Strasbourg, France: Council of Europe.Deardorff, D. K. (2011). Assessing intercultural competence. New Directions forInstitutional Research, 149, 65–79.DeMello, M. A. (2011). The impact of study tours in developing global-mindedness amongPK-12 educators in Southeastern Massachusetts (Doctoral dissertation, NortheasternUniversity, Boston)Duckworth, R. L., Levy, L. W., & Levy, J. (2005). Present and future teachers of theworld’s children How internationally-minded are they?. Journal of Research inInternational Education, 4(3), 279–311.Earley, P. C. and Ang, S. (2003). Cultural Intelligence: An Analysis of IndividualInteractions Across Cultures. Palo Alto (CA): Stanford University Press.Fantini, A. E. (2009), Assessing Intercultural Competence: Issues and Tools. In Deardorff,D. K. (ed.), The SAGE Handbook of Intercultural Competence. Thousand Oaks (CA):Sage, 456–476.FitzGerald, H. (2003). How Different Are We? Spoken Discourse in InterculturalCommunication. Clevedon – Buffalo – Toronto – Sydney: Multilingual Matters Ltd.Gaudelli, W. (2003). World class: Teaching and learning in global times. Mahwah, NJ:Erlbaum.Giddens, A. (1991) Modernity and Self-Identity. Cambridge: Polity.Gillian, K. J. (1995). A measure of global-mindedness at the University of NorthernColorado: An assessment of students, faculty, and administrators (Doctoral dissertation,University of Northern Colorado, 1995). Dissertation Abstracts International, 5,08.Hett, E. J. (1993). The development of an instrument to measure global-mindedness(Doctoral dissertation, University of San Diego).Hill, I. (2007). International education as developed by the International BaccalaureateOrganization. The SAGE handbook of research in international education, 25–37.Johnson, J. P., Lenartowicz, T., & Apud, S. (2006). Cross-cultural competence ininternational business: Toward a definition and a model. Journal of International BusinessStudies, 37(4), 525–543.Kehl, K., & Morris, J. (2007). Differences in global mindedness between short-term andsemester-long study abroad participants at selected private universities. Frontiers: TheInterdisciplinary Journal of Study Abroad, 15(1), 67–79.Lakoff, R. (1973). Language and woman's place. Language in society, 2(01), 45–79.Muller, G. C. (2012). Exploring characteristics of international schools that promoteinternational-mindedness (Doctoral dissertation, Teachers College, Columbia University).Olsen, M.E., Lodwick, D.G., & Dunlap, R.E. (1992). Viewing the World Ecologically.Boulder: Westview.Sampson, D. L., & Smith, H. P. (1957). A scale to measure world-minded attitudes. TheJournal of Social Psychology, 45(1), 99–106.Sercu, L. e.a. (2005). Foreign Language Teachers and Intercultural Competence. AnInternational investigation. Clevedon–Buffalo–Toronto: Multilingual Matters Ltd.Smallman, S. C., & Brown, K. (2011). Introduction to international & global studies.Chapel Hill: University of North Carolina Press.Wardhaugh, R. (1992). An Introduction to Sociolinguistics. USA: Blackwell PublishersLtd.Zhai, L., & Scheer, S. (2004). Global perspectives and attitudes toward cultural diversityamong summer agriculture students at the Ohio State University. Journal of AgriculturalEducation, 45(2), 39–51.